Data from: The earliest baleen whale of the mediterranean: Large-scale implications of an early miocene thalassotherian mysticete from Piedmont, Italy ... - Bisconti, Michelangelo; Damarco, Piero; Mao, Selina; Pavia, Marco; Carnevale, Giorgio (Dryad, 2020)
The discovery of an Early Miocene chaeomysticete from the Pietra da Cantoni Group in Piedmont (north-western Italy) allowed for the creation of Atlanticetus n. gen. and Atlanticetus lavei n. sp. The new species is represented by a partial skeleton including the earbones and shows anatomical resemblance with Atlanticetus patulus (new combination) from the western North Atlantic. The Early Miocene age of the new specimen supports the view that it represents the oldest record of Chaeomysticeti from the Mediterranean. A new phylogenetic analysis showed that both A. patulus and A. lavei belong to a radiation of basal thalassotherian taxa. The basal thalassotherians are found being monophyletic to the exclusion of Cetotheriidae and Balaenopteroidea. The reconstruction of ancestral characters at selected nodes informs that the group including Atlanticetus and living balaenopterid taxa independently evolved rostra wide at base, anterolateral expansion in the tympanic bulla and a peculiar arrangement of the ... : Anatomy, photography and measurements. The specimen studied is in the collection of the Museo Paleontologico Territoriale Astigiano (MPTA), Asti, Piedmont (north-west Italy) with the accession number 13301. The specimen includes a partially complete skeleton that was mechanically prepared and fixed using Paraloid. Measurements were taken with digital calipers Sourcingmap (300 mm) and Tacklife D02 (150 mm) both with error margin to the nearest 0.01 mm. Photography was made by using a Nikon D750 full frame DLSR with Tamron 90 mm f/2.8 Di VC macro lens. Light was provided by a Speedlight flash Nikon D700 with softbox mounted on the DSLR. Anatomical terms follow Mead & Fordyce (2009), Ekdale et al. (2011), and Martìnez-Cáceres et al. (2017). The comparative analysis included all the mysticete taxa listed in the Supplementary Information file that comprise most of the described species of living and fossil mysticetes belonging to all the baleen whale radiations. Anatomical abbreviations. Anatomical ...